A HARMONIZED EUROPEAN COMPANY LAW: ARE WE THERE ALREADY?. Issue 3 (25th May 2017) - Enriques, Luca
Abstract: To what extent is EU company law harmonized? This article first makes the point that little progress has been made in the direction of company law uniformity within the EU. It then argues that, even leaving aside the question of whether it would be desirable to have a uniform EU company law, that outcome is simply impossible to achieve, due to interest group resistance and the variety in national meta-rules. Yet it concludes that, in a narrow meaning, European company laws have indeed been harmonized: European Member States company laws fit together, which may well be what harmonization, not only etymologically, is all about.